Economics and Employment Generation of Bamboo-Based Enterprises: A Case Study from Eastern Bangladesh - Rana, M P; Mukul, Sharif A; Sohel, M S I; Chowdhury, M S H; Akhter, S; Chowdhury, M Q; Koike, M (Small-scale Forestry, 2010)
An exploratory survey was carried out to assess economics and employment generation of the trade of bamboo and bamboo-based secondary products in the eastern Bangladesh, to obtain reliable information about their status, socio-economic significance, production and marketing. The study was undertaken over 30 bamboo-based enterprises in a suburban market of eastern Bangladesh, to investigate regional product details, economic profitability and employment opportunities. The sample entrepreneurs, corresponding to about 25% of the bamboo enterprise population were interviewed using a semi-structured questionnaire. About 202 full and part-time workers were employed in the factories, under categories of artisan (who manufactured secondary products). The average number of worker’s in the large, medium and small factories were 9 (artisan 40%), 6.45 (artisan 35%) and 5 (artisan 25%) respectively. The study revealed that there was always a satisfied demand of skilled artisans. Most of the workers were relatively newly employed (not more than 5 years). The daily wage rate varied between 70 and 130 Tk. ($US 1 equals approximately 70 Bangladeshi Taka (Tk.), as at December 2008). Bambusa balcooa was the most utilized species (39.96%) in terms of monetary value. The price of a single B. balcooa culm in the local market was Tk. 160–210. Nine sizes of articles under seven bamboo categories were identified, these being bera (36″ × 120″ and 72″ × 96″), bookshelf (36″ × 24″), chaluni (12″ × 12″), chatai (48″ × 60″ and 36″ × 48″), jhuri , rickshaw hood and tukri . Net average profit per article was the highest for rickshaw hoods (Tk. 400 at the retailer stage). The total expected annual income for an enterprises from all articles types sold was estimated to be Tk. 85,800. Three distinct marketing channels were identified for selling bamboo and value-added secondary products. The study also generated policy implications for effective management of bamboo-based enterprises.